Generalized analytical body force model for actuator disc computations of wind turbines - Sørensen, Jens N (Wind Energy Science, 2023)
A new generalized analytical model for representing body forces in numerical actuator disc models of wind turbines is proposed and compared to results from a blade element momentum (BEM) model. The model is an extension of a previously developed load model, which was based on the rotor disc being subject to a constant circulation, modified for tip and root effects, corresponding to an optimum design case. By adding a parabolic circulation distribution, corresponding to a solid-body approach of the flow in the near wake, it is possible to take into account losses associated with off-design cases, corresponding to pitch regulation at high wind speeds. The advantage of the model is that it does not depend on any detailed knowledge concerning the actual wind turbine being analysed but only requires information about the thrust coefficient and tip-speed ratio. The model is validated for different wind turbines operating under a wide range of operating conditions. The comparisons show generally an excellent agreement with the BEM model even at very small thrust coefficients and tip-speed ratios.